Proposal of a new model for CL regression or maintenance during pregnancy on the basis of timing of regression of contralateral, accessory CL in pregnant cows (2017)
In bovine pregnancy, regression or maintenance of the corpus luteum (CL) is mediated through local communication pathways between embryo, uterus, and ovary with Days 16 to 25 of pregnancy generally recognized as the pivotal period determining either luteolysis or prevention of luteolysis. To evaluate this concept, accessory CL was generated by treating Holstein lactating dairy cows (n = 718) with GnRH on Day 5 of the first follicular wave to produce an accessory CL on the ovary either contralateral or ipsilateral to the gravid horn. In pregnant cows, 66.2% (86/130) of contralateral CL regressed by Day 75 of pregnancy, whereas few ipsilateral accessory CL regressed (11.9%; 8/67), on the basis of similar criteria (P < 0.0001). As hypothesized, some contralateral CL regressions (22/86 = 25.6%) happened on Days 19 to 25 of pregnancy. However, most contralateral CL regressions (64/86 = 74.4%) happened later than expected, from Days 33 to 60 of pregnancy. Later contralateral CL regression was more common in primiparous (84.3%) than multiparous (60.0%; P = 0.02) cows. Early accessory contralateral CL regression (Days 19–25) may be related to lack of exposure of the contralateral horn to interferon tau from the elongating embryo because pregnant cows without early accessory CL regression had a smaller uterine volume than nonpregnant cows or pregnant cows that had early accessory CL regression (128.4 ± 3.9 vs. 147.0 ± 3.8 vs. 143.6 ± 10.9 mm3, respectively; P = 0.003). These results indicate that there is a second distinct period for CL protection during bovine pregnancy from Days 30 to 60 and implicate local and not systemic pathways in occurrence or prevention of luteolysis during both the early (≤25 days) and later (≥33 days) critical periods since accessory contralateral CL regressed whereas the accessory ipsilateral CL of pregnancy remained.